CODE MIXING ON FACEBOOK AMONG MALAYSIAN TESL STUDENTS - ABDUL HALIM, HUZAINA (Advances in Social Sciences Research Journal, 2015)
Facebook which is one of the popular social networking sites has become a medium of communication and interaction for its users. This site popularity has aroused the researcher’s interest to choose it as a ground for this study. It has been identified that there is less study has been conducted particularly on the internet-based written texts Malaysia (Azirah, Norizah& Philip, 2012). The findings of this study have been believed would contribute and add to the literature in terms of code-mixing and education context since the participants were from TESL community. Data analysis would be based on the observation, Facebook status and wall interaction and lastly online open-ended questionnaire. The obtained data was analysed using the observation checklist, a tally sheet, as well as adapted and integrated frameworks by Ratna (2007) and Hoffman (1991) and also by Saville-Troike (2003) and Holmes (2001) for the reasons of code-mixing. Findings discovered that phrase insertion was the most frequent inserted level of code-mixing in Facebook while showing solidarity was the main reason of code-mixing in Facebook. This study which mainly focus on the participants’ way of communication in Facebook would be another root for other researchers to extend this kind of study henceforth focuses on other vital components of code-mixing that may persist when someone code-mixing in Facebook.